Effects of morphine or tramadol on thiopental anesthetic induction dosage and physiologic variables in halothane anesthetized dogs - Natalini, Cláudio Corrêa; Polidoro, Alexandre da Silva; Crosignani, Nadia (Acta Scientiae Veterinariae, 2018)
Eight dogs were premedicated with tramadol (1.0 mg/kg [0.45 mg/lb], IM) and the other eight with morphine (1.0 mg/kg [0.45 mg/lb], IM) 20 minutes prior to anesthetic induction. Anesthesia was induced with thiopental and maintained with halothane in oxygen delivered in a Bain system, with spontaneous respiration. Degree of sedation and occurrence of emesis were evaluated after preanesthetic medication. Dose of thiopental necessary to allow tracheal intubation was recorded and compared between the two groups. Arterial blood gas analyses were done before premedication and at 60 minutes of anesthesia. Tramadol produced no visible sedation and no vomit, while morphine induced a moderate degree of sedation in all dogs and vomit in 62% of them. Dose requirement of thiopental was significantly higher in the dogs premedicated with tramadol. Dogs premedicated with morphine had significantly higher PaCO 2 and lower pH at 60 minutes of anesthesia. Tramadol is not a reliable sedative and do not induce vomit in healthy dogs. The requirement of subsequent anesthetics may not be significantly reduced as compared with morphine. Dogs premedicated with tramadol are likely to maintain better intraoperative respiratory function than when premedicated with morphine. Clinically, tramadol may be useful for premedication of dogs where vomit is undesirable.